Development and evaluation of punching mechanism for de-seeding of ber fruit - Bharath Kumar Komatineni; B. Manjula; Sanwal Singh Meena; V. Kavan Kumar; Utkarsh Dwivedi; Akuleti Saikumar; Seelam Jaya Krishna; Sumit Kumar Vishwakarma (Discover Agriculture)
Abstract Ber (Ziziphus mauritiana L.) commonly known as Indian jujube, is an underutilized seasonal fruit rich in nutrients and consumed directly. A punching type mechanism was developed to separate the seed and pulp of ber fruit, based on the analysis of its physical (length, width, thickness measured by vernier caliper) and mechanical properties (cutting and extruding forces measured by texture analyzer). The Pearson correlation coefficient showed that the physical parameters (width, thickness, geometric mean diameter, arithmetic mean diameter) were strongly correlated with the sphericity and surface area of the ber fruits and seeds, whereas length was not significantly correlated. The developed punching type de-seeding mechanism consists of a fruit resting seat, punching rod, guider, crank and lever mechanism, supporting stand, handle, and base. The performance of the developed de-seeder was analyzed, showing fruit pulp wastage from 1.89% to 8.62% and efficiency from 91.38% to 98.11%. The Pearson correlation coefficient indicated that the performance parameters (pulp wastage and efficiency) of de-seeder are negatively correlated. The capacity of the developed de-seeder varies from 15 – 17 kg/ h and 220 – 280 fruits/ h. The developed de-seeder reduces the labour requirement by 67%. In economic evaluation, the de-seeder has reduced the cost of operation (₹ h−1) by 73% and increase the net benefit (₹ year−1) by 6960 over manual operation. Its high efficiency and less pulp wastage make the machine preferable for progressive farmers. Graphical Abstract